PEOPLING OF OCEANIA: CLARIFYING AN INITIAL SETTLEMENT HORIZON IN THE MARIANA ISLANDS AT 1500 BC. Issue 6 (1st December 2020) - Carson, Mike T
ABSTRACT: Radiocarbon ( 14 C) has been instrumental in clarifying how people came to inhabit the expanse of Pacific Oceania, now supporting an "incremental growth model" that shows a number of long-distance sea-crossing migrations over the last few millennia. A crucial step in this narrative involved the initial settlement of the remote-distance Oceanic region, in the case of the Mariana Islands around 1500 BC. The Marianas case can be demonstrated through delineation of stratigraphic layers, dating of individual points or features within those layers, redundant dating of samples in secure contexts, localized and taxon-specific corrections for marine samples, and cross-constraining dating of superimposed layer sequences. Based on the technical and methodological lessons from the Marianas example, the further steps of the incremental growth model will continue to be refined across Pacific Oceania. Many of these issues may be relevant for broader research of ancient settlement horizons in other regions.